Disaggregating health inequalities within Rio de Janeiro, Brazil, 2002-2010, by applying an urban health inequality index - Bortz, Martin; Kano, Megumi; Ramroth, Heribert; Barcellos, Christovam; Weaver, Scott R.; Rothenberg, Richard; Magalhães, Monica; Bortz, Martin; Ramroth, Heribert (Cadernos de saúde pública, 2015)
AbstractAn urban health index (UHI) was used to quantify health inequalities within Rio de Janeiro, Brazil, for the years 2002-2010. Eight main health indicators were generated at the ward level using mortality data. The indicators were combined to form the index. The distribution of the rank ordered UHI-values provides information on inequality among wards, using the ratio of the extremes and the gradient of the middle values. Over the decade the ratio of extremes in 2010 declined relative to 2002 (1.57 vs. 1.32) as did the slope of the middle values (0.23 vs. 0.16). A spatial division between the affluent south and the deprived north and east is still visible. The UHI correlated on an ecological ward-level with socioeconomic and urban environment indicators like square meter price of apartments (0.54, p < 0.01), low education of mother (-0.61, p < 0.01), low income (-0.62, p < 0.01) and proportion of black ethnicity (-0.55, p < 0.01). The results suggest that population health and equity have improved in Rio de Janeiro in the last decade though some familiar patterns of spatial inequality remain.Key words: Health Status Indicators; Health Inequalities; Urban Health